Intercultural adaptation in returned migrants: A study in Zacatecas, Mexico - Tovar Chávez , Dulce María Fernanda (Consorcio de Universidades Mexicanas A.C., 2018)
Due to the consequences and possible everyday life implications, such as a job search, social and cultural relationships and economic problems (Centro Internacional de Derechos Humanos de los Migrantes [CIDEHUM], 2011), migration has become a complex phenomenon (Serafi, 2006). Given these implications, migrants attempt to fully integrate to the dominant culture while still keeping their cultural identity (Casasa, 2008). To do so migrants seek people belonging to their city of origin, thus creating a transnational community (Sassone, 2007). The current manuscript used qualitative methods to identify the main problems arising from intercultural adaptations in returned Mexican migrants. Learning and experiences in their social environment were also explored. Five migrants who returned from the United States to their hometown (Fresnillo, Zacatecas, Mexico), were interviewed. Results demonstrate that the main problems faced related to cultural adaptation were language barriers, lack of citizenship paperwork and workplace exploitative practices.